Current status and opportunities for therapeutic drug monitoring in the treatment of tuberculosis. (3rd May 2016) - Zuur, Marlanka A.; Bolhuis, Mathieu S.; Anthony, Richard; den Hertog, Alice; van der Laan, Tridia; Wilffert, Bob; de Lange, Wiel; van Soolingen, Dick; Alffenaar, Jan-Willem C.
ABSTRACT: Introduction: Tuberculosis remains a global health problem and pharmacokinetic variability has been postulated as one of the causes of treatment failure and acquired drug resistance. New developments enable implementation of therapeutic drug monitoring, a strategy to evaluate drug exposure in order to tailor the dose to the individual patient, in tuberculosis treatment. Areas covered: Literature on pharmacokinetics and pharmacodynamics of anti-tuberculosis drugs was explored to evaluate the effect of drug exposure in relation to drug susceptibility, toxicity and efficacy. New, down-sized strategies, like dried blood spot analysis and limited sampling strategies are reviewed. In addition, molecular resistance testing of Mycobacteria tuberculosis, combining a short turn-around time with relevant information on drug susceptibility of the causative pathogen was explored. Newly emerging host biomarkers provide information on the response to treatment. Expert opinion: Therapeutic drug monitoring can minimize toxicity and increase efficacy of tuberculosis treatment and prevent the development of resistance. Dried blood spot analysis and limited sampling strategies, can be combined to provide us with a more patient friendly approach. Furthermore, rapid information on drug susceptibility by molecular testing, and information from host biomarkers on the bacteriological response, can be used to further optimize tuberculosis treatment.